Enhanced magnetocaloric effect of Sr1.8Eu0.13Ba0.07FeMoO6 perovskite compound. Issue 3 (15th February 2018) - Hu, Yanchun; Li, Weixia; Wang, Xianwei; Cui, Yawen; Wei, Yuting; Sun, Lingyun; Guo, Tengyu; Zhao, Xiangyu
Abstract: Double perovskite (Sr1.8 Eu0.13 Ba0.07 )FeMoO6 (SEBFMO) as well as Sr2 FeMoO6 (SFMO) were prepared by the traditional solid reaction method. X-ray diffraction results show that all compounds are single phase, which belongs to I4/ m space group. The magnetic hysteretic loops (M-H) and field-cooled magnetization (FC) curves indicate that all compounds have good ferromagnetic properties. The FC curves show a phase transition temperature at around 370 K. The Arrot plots (H/M-M 2 ) of samples show that a second-order magnetic transition has occurred. An enhanced magnetocaloric effect was observed in SEBFMO. The maximum isothermal magnetic entropy change of SEBFMO reaches to 0.76 J kg −1 K −1 for ∆H = 3 T, but that of SFMO only reaches to 0.50 J kg −1 K −1 .